ANALISIS PERLAKUAN AKUNTANSI GADAI EMAS SYARIAH PADA PT. BANK SYARIAH CABANG MAKASSAR - Ramli, Riskawati; Sriwahyuni, Sriwahyuni (Jurnal Ar-Ribh, 2018)
This study aims to determine the suitability of the accounting treatment of mortgage financing of sharia gold in bank BTN Syariah with PSAK 107 (Akad Ijarah) The type of research used in this research is descriptive qualitative.As data collection techniques conducted by the author is by observation, interview and Documentation and using data in the form of accounting guidance that is PSAK 107 (Revision 2015), analysis technique using data reduction techniques, data display and data verification. The result of the research indicates that the product of BTN iB Gold Pawn has run the accounting guidance of PSAK 107, and has been in accordance and refer to PSAK 107 (aka ijarah).